Health related quality of life is differently associated with leisure-time physical activity intensities according to gender: a cross-sectional approach - Nakamura, Priscila Missaki [UNESP]; Teixeira, Inaian Pignatti [UNESP]; Caraca Smirmaul, Bruno Paula [UNESP]; Sebastiao, Emerson; Papini, Camila Bosquiero [UNESP]; Gobbi, Sebastiao [UNESP]; Kokubun, Eduardo [UNESP] (Biomed Central Ltd, 2014)
Background: Several studies have demonstrated a positive association between physical activity (PA) and health-related quality of life (HRQL). However, studies have suggested that this association depends both on the PA intensity and the domain of HRQL evaluated. This study aimed to explore the association between physical, mental and overall HRQL with recommended levels of PA. PA levels were divided into moderate and vigorous intensity leisure-time PA and total leisure-time PA.Methods: The study included 1001 adults, 582 women (46 +/- 17 years) and 419 men (43 +/- 16 years), residents in Rio Claro-SP, Brazil. All participants completed the SF-36 questionnaire to assess HRQL and the long version of the International Physical Activity Questionnaire (IPAQ) to assess level and intensities of leisure-time PA. Total leisure-time PA at moderate intensity was classified as: less than 9 min/week, 10-149 min/week, 150-299 min/week and 300 min/ week or more. Total leisure-time PA at vigorous intensity was classified as: less than 9 min/week, 10 to 74.9 min/week, 75-149 min/week and 150 min/week or more. Multiple linear regression was performed in STATA version 12.0.Results: Among women, moderate intensity and total leisure-time PA were associated with physical health. Among men, moderate and vigorous intensity and total leisure-time PA were associated with physical health and overall HRQL. Furthermore, moderate intensity and total leisure-time PA were associated with mental health in men. However, vigorous intensity PA was not associated with mental health for this group.Conclusion: The different domains of HRQL were associated with different levels and intensities of PA in leisure-time according to gender of adults. These findings indicate the complexity and importance of evaluating the HRQL stratified by gender and consider the different levels and intensities of PA.
Keywords: Health-related quality of life; Adult; Intensities of physical activity; Brazil; Mental health; Physical health